Industrial Relations in the Plantation Sector: A Study on Dismissal Cases in the Plantations from 1974 to 1994 - Rohany, Habibah (1997)
It is important that a study on the industrial relations aspect of the plantation sector is conducted especially with regards to the welfare and status of the plantation workforce after an unfair dismissal because there is a lack of analysis of the relative position of those who seek reinstatement or compensation in lieu of reinstatement. This initiated the study on the factors that contribute to the unfair dismissals of all levels of the plantation workforce with the objective of understanding further whether these factors identified in the study are justified to be the causes of unfair dismissal. It is also important to highlight that while misconduct is the contributory factor of dismissal of a plantation worker, not all causes are entirely committed by the dismissed worker but also the employer. Thus other aspects of dismissals are also studied such as procedural defects of domestic inquiry, weaknesses and problems of representations and enforcement of the Industrial Relations Act 1967. The data collected for the purpose of this study are the court cases illustrated in the Industrial Law Report from 1974 to 1994. Both descriptive and statistical analyses were conducted. The types of misconduct differed throughout the twenty years, absenteeism was the main cause in the seventies, insubordination and fraud or malpractice in the eighties and nineties. The Correlation Analysis showed that when a worker is dismissed for insubordination, he is also unfairly accused of verbal abuse or physical assault, a tactic to substantiate further dismissal of the worker. While acts of major or serious misconducts contribute to an instant dismissal, the findings of the Qualitative Regression Analysis, however, shows that dismissal is not due to acts of major misconduct only. The Multivariate Factor Analysis, in fact, also shows that acts of moderate or minor misconducts also contributed to dismissal of a worker. In the plantations sector, a domestic inquiry must be conducted before a worker is dismissed. However, an analysis on the conduct of the domestic inquiry held in all the cases from 1974 to 1994 shows that 50% of the cases had an unfair inquiry. A further analysis shows that 62.9% of the cases show harsh and unfair application of the industrial law in the court awards. The trend of court awards also shows that a worker who seeks reinstatement most often will be compensated in lieu of reinstatement. This is also another cause of concern because until 1994, 54.5% of the dismissed workers are from the lowest category of plantation workers who prefer reinstatement to compensation. The findings of this study should benefit all parties because it has highlighted important aspects of industrial relations in the plantation sector. There is a change in the pattern of acts of misconduct in the plantation industry from theft, physical acts of disobedience and dishonesty to more subtle acts of insubordination and fraud. This may be due to the increase in the dismissals of the other levels of the plantation workforce. Taking into account the acts of misconduct by both the non-executive and executive levels of the plantation workforce, the employers should establish a more detailed guideline as to what constitutes acts of major misconduct serious enough to warrant instant dismissal and acts of moderate and weak misconduct that could also lead to instant dismissal. The management must also ensure that a proper procedure of the domestic inquiry is conducted because failure to do so reflects the weakness of management. From the analysis of the study, there is also a delay in both the time period, from the date of dismissal to the date of reference to court and from the date of reference to court to the date of court award. A further analysis indicate that it is more serious in the second time period. Not enough efforts have been done to expedite settlement of these cases and there is a dire need for a better and faster method of settling these court cases. As such any weaknesses of the procedures in the industrial relations system should be reviewed or taken into consideration and improved.